Discovering Key Topics From Short, Real-World Medical Inquiries via Natural Language Processing - Ziletti, A.; Berns, C.; Treichel, O.; Weber, T.; Liang, J.; Kammerath, S.; Schwaerzler, M.; Virayah, J.; Ruau, D.; Ma, X.; Mattern, A. (Frontiers in Computer Science, 2021)
Millions of unsolicited medical inquiries are received by pharmaceutical companies every year. It has been hypothesized that these inquiries represent a treasure trove of information, potentially giving insight into matters regarding medicinal products and the associated medical treatments. However, due to the large volume and specialized nature of the inquiries, it is difficult to perform timely, recurrent, and comprehensive analyses. Here, we combine biomedical word embeddings, non-linear dimensionality reduction, and hierarchical clustering to automatically discover key topics in real-world medical inquiries from customers. This approach does not require ontologies nor annotations. The discovered topics are meaningful and medically relevant, as judged by medical information specialists, thus demonstrating that unsolicited medical inquiries are a source of valuable customer insights. Our work paves the way for the machine-learning-driven analysis of medical inquiries in the pharmaceutical industry, which ultimately aims at improving patient care.